2021
DOI: 10.1017/s0261143021000118
|View full text |Cite
|
Sign up to set email alerts
|

Sonic branding and the aesthetic infrastructure of everyday consumption

Abstract: Sonic branding – the sonic expression of a brand's identity – is the audio equivalent of a brand's logo, a sound that is both distinct and adaptable to diverse contexts, and serves to communicate a brand's narrative. Sonic branding has been a feature of marketing strategies for the past two decades, but more recently there has been increased commercial interest in sonic branding, a move from the ‘visual turn’ to the ‘sonic turn’, as voice activation technologies such as Siri, Amazon's Alexa and Google Assistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…sonic logos, sounds of brand names) can effectively communicate brand identity by implying extra-acoustic information (e.g. competence) about the brand (Khamis and Keogh, 2021; Gustafsson, 2015). In a similar vein, previous research on human voices has demonstrated that a speaker's voice conveys extra-acoustical associations with the speaker (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…sonic logos, sounds of brand names) can effectively communicate brand identity by implying extra-acoustic information (e.g. competence) about the brand (Khamis and Keogh, 2021; Gustafsson, 2015). In a similar vein, previous research on human voices has demonstrated that a speaker's voice conveys extra-acoustical associations with the speaker (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Sonic Agency DLMDD, in a study that was conducted in cooperation with market research firm YouGov, found that 20% of young adults were more inclined to buy a product from a brand with a sonic identity as compared to those without, and one in three young adults feel more positive towards those brands that have a distinctive sonic identity (McCullough, 2023). Mastercard and GfK Global reported that within 12 months of the launch of their sonic brand identity, 77% of their consumers believed that the new sonic identity made the brand more trustworthy (BrandMusiq, 2022; Cozine, 2020; Khamis & Keogh, 2021), whereas Tostidos reported a 38% increase in brand recall, a 13% increase in brand score, and a 70% increase in overall appeal after the launch of their sonic logo, based on market research conducted by audio testing company Veritonic (Made Music Studio, 2022; see also Cakim, 2023).…”
Section: Introductionmentioning
confidence: 99%